Electrochemical studies of gold and chloride in ionic liquids - Aldous, L.; Silvester, Debbie; Villagran, C.; Pitner, W.; Compton, R.; Lagunas, M.; Hardacre, C. (Royal Society of Chemistry, 2006)
For the first time, the electrochemistry of gold has been studied in detail in a ‘second-generation’, non-haloaluminate, ionic liquid. In particular, the electrochemical behaviour of Na[AuCl4] has been investigated in 1-butyl-3-methylimidazolium bis{(tifluoromethyl)sulfonyl}imide, [C4mim][NTf2], over gold, platinum and glassy carbon working electrodes. The reduction of [AuCl4] initially forms [AuCl2] before deposition on the electrode as Au(0). To enable stripping of deposited gold or electrodissolution of bulk gold, the presence of chloride, trichloride or chlorine is required. Specifically trichloride and chlorine have been identified as the active species which preferentially form Au(I) and Au(III), respectively.